Professional SharePoint® 2013 administration - Young, Shane (John Wiley & Sons, Inc. IndianaUS, 2013)
Focuses primarily on traditonal SharePoint administration topics, including architecture and capacity planning, installing and configuring SharePoint; claims authentication and OAUTH, adminstering SharePoint with Windows PowerShell, configuring SharePoint for business intelligence; managing and configuring apps, branding SharePoint; working with SharePoint Designer; troubleshooting SharePoint; configuring and managing web content.